Offspring sex ratio increases with paternal reproductive success in a colony of southern elephant seals - Hassen Allegue; Christophe Guinet; Samantha C. Patrick; Cécile Ribout; Coraline Bichet; Olivier Lepais; Denis Réale (Marine Mammal Science, 2024)
In polygynous species, male reproductive success is often determined by their ability to dominate female harems. Harem‐holders sire a disproportionate number of offspring. Male dominance tends to correlate with age, but intense competition and early male mortality limit most males from achieving high social status. To maximize reproductive success despite low rank, offspring sex ratio adjustment may have evolved, favoring the sex with higher fitness. If traits influencing dominance are heritable and confer reproductive advantages, we expect fathers with higher reproductive success to produce more sons, as they are more likely to become dominant. In contrast, subordinate males with lower success may benefit from siring more daughters. We tested this hypothesis on a colony of southern elephant seals breeding on the Kerguelen Archipelago. We used genetic markers to link the paternity of 540 pups to 58 breeding males. We found that the probability of siring a son increases from 43% to 54% with paternal relative reproductive success, supporting the offspring sex ratio adjustment hypothesis. Given that various factors influence sex ratio in a population, future studies should tease apart these ecological processes (e.g., paternal dominance, maternal condition, local density, or adult sex ratio) and investigate how they interact with each other.

WISE-2005: effect of aerobic and resistive exercises on orthostatic tolerance during 60 days bed rest in women - Patrick Guinet; Suzanne M. Schneider; Brandon R. Macias; Donald E. Watenpaugh; Richard L. Hughson; Anne Pavy Le Traon; Jean-Yves Bansard; Alan R. Hargens (European Journal of Applied Physiology, 2009)